Biochemical characterisation and application of lipases produced by Aspergillus sp on solid-state fermentation using three substrates - Fleuri, Luciana Francisco [UNESP]; Novelli, Paula K. [UNESP]; Delgado, Clarissa H. O. [UNESP]; Pivetta, Mayara R. [UNESP]; Pereira, Milene S. [UNESP]; Arcuri, Mariana de L. C. [UNESP]; Capoville, Bruna L. [UNESP] (Wiley-Blackwell, 2014)
Lipase from Aspergillus sp. obtained by solid-state fermentation (SSF) on wheat bran (LWB), soybean bran (LSB) and soybean bran combined with sugarcane bagasse (LSBBC) were 67.5, 58 and 57.3U of crude lipase per gram substrate, respectively. The optimum pH of activity and stability of the LWB was between 8 and 9, and the optimum temperature of activity and stability was 50 degrees C and up to 60 degrees C, respectively. The LSB and LSBBC showed two peaks of optimum pH (4 and 6) and optimal values of temperature and stability at 50 degrees C. The LSB was stable in the pH range of 6-7, while LSBBC in the range of pH 4-7. All the enzymes show activities on p-nitrophenyl esters (butyrate, laurate and palmitate). LWB stood out either on the hydrolysis of sunflower oil, presenting 66.1% of the activity over commercial lipase and on the esterification of oleic acid and ethanol, surpassing the activities of the commercial lipases studied. The thin layer chromatography showed that LWB and LSB have produced ethyl esters from corn oil, while LWB produced it from sunflower oil.
Keywords: Aspergillus sp; esterification; lipase; soybean bran; sugarcane bagasse; wheat bran